Development of precision therapies for rare inborn errors of metabolism: Functional investigations in cell culture models - Didiasova, Miroslava; Banning, Antje; Tikkanen, Ritva; Justus Liebig University Giessen (My University, 2024)
Due to the low number of patients, rare genetic diseases are a special challenge for the development of therapies, especially for diseases that result from numerous, patient-specific pathogenic variants. Precision medicine makes use of various kinds of molecular information about a specific variant, so that the possibilities for an effective therapy based on the molecular features of the variants can be elucidated. The attention to personalized precision therapies has increased among scientists and clinicians, since the “single drug for all patients” approach does not allow the classification of individuals in subgroups according to the differences in the disease genotype or phenotype. This review article summarizes some approaches of personalized precision medicine that can be used for a cost-effective and fast development of therapies, even for single patients. We have focused on specific examples on inborn errors of metabolism, with special attention on drug repurposing. Furthermore, we provide an overview of cell culture models that are suitable for precision medicine approaches.
Keywords: drug repurposing; inborn errors of metabolism; pathogenic variants; personalized medicine; precision medicine; rare diseases; ddc:610